Peer conformity, attention, and heterogeneous implementation of practices in MNEs - Durand, Rodolphe; Jacqueminet, Anne (Journal of International Business Studies, 2015)
How do subsidiaries respond to normative demands from both their headquarters and local external constituents? We propose that subsidiaries pay varying levels of attention to demands depending on their peers’ norm-conforming behavior, resulting in heterogeneous practice implementation. We study the implementation of 25 practices, associated with three corporate social responsibility (CSR) issues in 101 worldwide subsidiaries of a multinational enterprise (MNE). Consistent with the idea that attention is limited and therefore selective, we find that external peers’ conformity to the CSR norm directs subsidiaries’ attention toward the CSR-related demands of external constituents at the expense of the demands from the headquarters. However, internal peers’ conformity increases attention to both external and headquarters’ demands related to CSR. As higher attention levels result in higher practice implementation, internal and external peers’ conformity drives the heterogeneity of practice implementation in the MNE. Our results suggest the need to rethink the influence of peers’ conformity on subsidiaries’ implementation of practices, as it not only triggers mimicry based on legitimacy but also and simultaneously a more strategic response based on internal and external competitive threats and attention allocation.